Validation of soil moisture data from the Lena Delta retrieved by satellite. - Högström, Elin; Heim, Birgit; Bartsch, Annett (PANGAEA, 2018)
Four automatic stations measuring soil temperature and VWC were deployed in the central Lena River Delta, Siberia in August 2013 and retrieved in August 2014. They were installed in a very shallow depth on the islands Kurungnakh and Samoylov. Three stations were placed on Kurungnakh (K1, K2, K3) and one on Samoylov (S1). Each station on Kurungnakh consisted of a) one VWC Campbell Recording Sensors CR625 and one Temperature T109 sensor at the most upper depth one (W1 and T1), b) one VWC CR625 sensor and one T109 sensor at depth two (W2 and T2; Figure 1C). The station on Samoylov had the same setup as those on Kurungnakh, with the exception that only one depth could be instrumented (W1 and T1). The sensors at depth one were placed in the lower end of the uppermost porous moss layer (in average of 5 to 7 cm thickness). The sensors at depth two were placed in the moss fibric layer, a thin layer of ca 2 to 3 cm which is the water storage layer of the moss and mostly water saturated. The field work in the Lena Delta has been supported by two scholarships for transnational access (2013 and 2014) of the International Network for Terrestrial Research and Monitoring in the Arctic (FP7 INTERACT). The data have been analyzed for satellite derived soil moisture within the framework of the FP7 project PAGE21.
Near surface volumetric soil moisture and temperature measurements in the Lena Delta for 2013/2014
Keywords: AWI_PerDyn; Changing Permafrost in the Arctic and its Global Effects in the 21st Century; PAGE21; Permafrost Research (Periglacial Dynamics) @ AWI